PENGARUH KADAR AIR TERHADAP BESARNYA PENURUNAN PADA UJI KONSOLIDASI - Ayu Purnama Sari; M. Ikhwan Yani; Suradji Gandi (Universitas Lambung Mangkurat, 2021)
Clay soil is a cohesive soil with low bearing capacity and low shear strength where the load on it will be limited. The addition of water content in clay soil will result in changes in soil volume that will affect the strength of the soil. The research aims to know how much water content affects the values of consolidation settlement. A consolidation test was carried out three times with variations of the original soil sample, 35% water content and 30% water content. The results obtained a settlement of 0,1864 cm for original water content, 0,1677 cm for 35% water content, and 0,1414 cm for 30% water content.